A Large Spanish-Catalan Parallel Corpus Release for Machine Translation - Costa-Jussà, Marta R.; Fonollosa, José A. R.; Mariño, José B.; Poch, Marc; Farrús, Mireia (COMPUTING AND INFORMATICS, 2015)
We present a large Spanish-Catalan parallel corpus extracted from ten years of the paper edition of a bilingual Catalan newspaper. The produced corpus of 7.5 M parallel sentences (around 180 M words per language) is useful for many natural language applications. We report excellent results when building a statistical machine translation system trained on this parallel corpus. The Spanish-Catalan corpus is partially available via ELDA (Evaluations and Language Resources Distribution Agency) in catalog number ELRA-W0053.